Effects of probiotic supplementation on selected health indices among a group of competitive cyclists (effect of probiotic therapy on health indices) - Mazur-Kurach, P.; Sobon, T.; Klimek, A.; Fraczek, B.; Klimek-Jelonek, A. (Journal of Kinesiology and Exercise Sciences, 2020)
Introduction: In scientific reports from recent years, a significant relationship is clearly indicated between the intestinal microbiota and chronic diseases, and the role of selected probiotic strains is emphasized not only in maintaining good health, but also in achieving optimal physical fitness among athletes. Aim: The aim of the study was to assess the impact of supplementation with multi-strain probiotics on selected health indices among professional road cycling competitors. Material and methods: The study group comprised cyclists aged 18-26 (N=26), randomly assigned to 2 subgroups: experimental (n=13) and control (n=13), who were administered a multi-strain probiotic or a placebo for 4 months. The experiment was a double-blinded, randomised trial. Assessment of health status, within the context of analysing selected values of haematological and biochemical indices of the blood, urine and faeces, was performed before the examination, after 1 month, 3 months and following completion of the experiment. Results: The 16-week intervention of supplementation with a probiotic preparation was associated with a change in some biochemical blood indices of the studied men. Decreases in the concentration of total protein and alkaline phosphatase were found. The applied 4-month supplementation did not affect the levels of haemoglobin, glucose, keratin kinase or total cholesterol, HDL, LDL and triglycerides. Probiotic supplementation contributed to inhibiting the growth of intestinal pathogenic bacteria, simultaneously influencing the growth of selected strains of symbiotic bacteria. The changes in the values of the indices measured before and after the end of the experiment and between the groups, were not statistically significant. Conclusions: The assessed blood indices in both subgroups were within the reference ranges, both before starting the probiotic/ placebo and after the supplementation period. The demonstrated changes in the index values suggest a beneficial effect of the probiotic preparation on the composition of the faecal microbiota.